From clinical management to personalized medicine: novel therapeutic approaches for ovarian clear cell cancer - Zesi Liu; Chunli Jing; Fandou Kong (BMC, 2024)
Abstract Ovarian clear-cell cancer is a rare subtype of epithelial ovarian cancer with unique clinical and biological features. Despite optimal cytoreductive surgery and platinum-based chemotherapy being the standard of care, most patients experience drug resistance and a poor prognosis. Therefore, novel therapeutic approaches have been developed, including immune checkpoint blockade, angiogenesis-targeted therapy, ARID1A synthetic lethal interactions, targeting hepatocyte nuclear factor 1β, and ferroptosis. Refining predictive biomarkers can lead to more personalized medicine, identifying patients who would benefit from chemotherapy, targeted therapy, or immunotherapy. Collaboration between academic research groups is crucial for developing prognostic outcomes and conducting clinical trials to advance treatment for ovarian clear-cell cancer. Immediate progress is essential, and research efforts should prioritize the development of more effective therapeutic strategies to benefit all patients.